2014
DOI: 10.5152/dir.2014.13382
|View full text |Cite
|
Sign up to set email alerts
|

Management of visceral artery embolization using 0.010-inch detachable microcoils

Abstract: Transcatheter coil embolization is used primarily to treat arterial hemorrhages, tumors, aneurysms, and vascular malformations. However, conventional microcatheter systems cannot always be employed in difficult cases. In this technical note, we describe how small-diameter primary coils and microcatheter tips that are thinner than normal can be used to increase the safety and reliability of coil embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…In addition, coils should have been sized 20%-30% larger than the size of the vessel as measured on a pre-deployment angiogram to prevent distal embolization or migration, as the placement of an undersized coil risks its distal embolization away from the intended location (24). Koganemaru et al (27) reported that small-diameter primary coils and microcatheter tips that are thinner than normal can be used to increase the safety and reliability of coil embolization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, coils should have been sized 20%-30% larger than the size of the vessel as measured on a pre-deployment angiogram to prevent distal embolization or migration, as the placement of an undersized coil risks its distal embolization away from the intended location (24). Koganemaru et al (27) reported that small-diameter primary coils and microcatheter tips that are thinner than normal can be used to increase the safety and reliability of coil embolization.…”
Section: Discussionmentioning
confidence: 99%
“…or smaller. [6][7][8][9] The triaxial system was previously shown to be useful for super-selective catheterization under various conditions. 5 In particular, it should be very effective for cases which definitely need super-selective catheterization, such as those with pseudoaneurysm, gastrointestinal bleeding, or type 2 endoleak after EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…microcatheters in embolization of the visceral artery has been demonstrated. 6 The inner space of 1.7-Fr. microcatheters is small, which necessitates the use of 0.010-in.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the identification of at least 20% of coil dense packing to reduce the risk of aneurysm recanalization [26]. In case of tight packing density with covered of long tracts of efferent and afferent artery to SAA, the acute exclusion of splenic circulation can potentially lead to splenic infarction [27][28][29]. The employed Concerto Helix Detachable Coil System (Medtronic, Inc.) are constructed of a platinum embolization coil linked to a pushable delivery system enclosed to the spiral.…”
Section: Stem Cell Res Int 2023mentioning
confidence: 99%